Key changes in indices of myocardial work in cardiometabolic disease states. (25th November 2020) - Chen, H.H.L; Bhat, A; Chandrakumar, D; Fernandez, F; Kodsi, M; Gan, G; Tan, T.C
Abstract: Background: Hypertension (HTN) and diabetes mellitus (DM) are prevalent cardiovascular disease states which have been shown to be associated with adverse cardiac remodelling and subclinical myocardial dysfunction. Myocardial work (MW) indices are novel non-invasive measures of left ventricular (LV) function. We aimed to characterise key differences in MW indices in patients with these conditions. Methods: Outpatients with HTN and DM undergoing transthoracic echocardiography (TTE; 2016–2019) at our institution were assessed and compared to healthy controls. Only patients without cardiac disease with normal diastolic parameters on TTE were recruited. Patients with impaired LV function, cardiac ischaemia or arrhythmia, structural and valvular heart disease or poor-quality images were excluded. Recruited patients were stratified into 3 groups (Group1: Healthy Controls; Group 2: HTN; Group 3: HTN-DM). MW assessment was performed using GE E-95 EchoPac v2.2 system. Results: Three hundred patients (57.3±17.4y, 51% female) were recruited. HTN and HTN-DM patients were associated with higher resting systolic blood pressure (SBP), indexed LV mass (LVMI), e' and E/e' compared to controls but no differences were noted in these parameters between HTN and HTN-DM. Global myocardial work index (GWI) was higher in HTN patients compared to Controls but not different compared to HTN-DM. Of interest, HTN-DM patients had higher global myocardial wasted work (GWW) and lower global myocardial work efficiency (GWE) compared to HTN patients and Controls. Conclusions: MW indices may be a sensitive tool for the detection of subclinical changes in cardiac function in cardiometabolic disease states. Funding Acknowledgement: Type of funding source: None